Enhanced Sliding Wear Resistance of Technical Alloys by Hard Particle Reinforcement Using Machine Hammer Peening. Issue 3 (4th May 2017) - Rodríguez Ripoll, Manel; Heindl, Franz; Lechner, Christoph; Totolin, Vladimir; Jech, Martin; Bleicher, Friedrich
ABSTRACT: Machine hammer peening is a surface treatment technique originally developed for smoothening tools and mold surfaces. Treated surfaces are locally cold-worked, which results in a hardness increase and the induction of compressive residual stresses. In the present work, the feasibility of using this technique as a tool for embedding tungsten carbide hard particles on engineering-relevant substrate materials is systematically investigated. Tungsten carbide particles of three different sizes were embedded onto selected substrates using machine hammer peening. The particle embedment quality of the engineered surfaces was evaluated and correlated to the substrates' mechanical properties. The resulting tribological performance was investigated under reciprocating sliding conditions and the dominant wear mechanisms were correlated with the diameter of the embedded particles. The results show that machine hammer peening is a suitable technique for embedding hard particles in substrates of various materials, which additionally results in an enhancement in wear resistance, thus opening up a wide range of potential applications in tribologically loaded surfaces.